Ongoing declines for the world’s amphibians in the face of emerging threats - Jennifer A., Luedtke; Janice, Chanson; Kelsey, Neam; Louise, Hobin; Adriano O., Maciel; Alessandro, Catenazzi; Amaël, Borzée; Amir, Hamidy; Anchalee, Aowphol; Indraneil, Das (Springer Nature, 2023)
Systematic assessments of species extinction risk at regular intervals are necessary for informing conservation action1,2. Ongoing developments in taxonomy, threatening processes and research further underscore the need for reassessment3,4. Here we report the findings of the second Global Amphibian Assessment, evaluating 8,011 species for the International Union for Conservation of Nature Red List of Threatened Species. We find that amphibians are the most threatened vertebrate class (40.7% of species are globally threatened). The updated Red List Index shows that the status of amphibians is deteriorating globally, particularly for salamanders and in the Neotropics. Disease and habitat loss drove 91% of status deteriorations between 1980 and 2004. Ongoing and projected climate change effects are now of increasing concern, driving 39% of status deteriorations since 2004, followed by habitat loss (37%). Although signs of species recoveries incentivize immediate conservation action, scaled-up investment is urgently needed to reverse the current trends.